Desenho, teatro e educação: interpretações da ação dramática através do traço - Santana, Renato Tavares (2014)
The proposal of this work involves the interaction-integration between Design and Theatre and its implication to Education, recognizing and exploiting the potential of these knowledge transformers. Art, Education, Art and Theatre are more than words, are powerful concepts that are completely interwoven in a world that is not fragmented but dynamic and interactive. The prospect of Edwards (2000), Ferreira and Santos (2000), Gomes (1996), Moreira (2009) and Tiburi and Chui (2010), identified the drawing as poetry and mystery, but also as language, creating, thinking, intention and design (which materializes in the mind of every individual or in outer reality) and therefore is present in all areas of knowledge and human experience. The ideas of Pavis (2008) reveal a theater living experience, that enables a collective design, an ongoing dialogue between tasks, knowledge and various individuals. The research has developed an analysis of drawings produced by students of high school volunteers, on the proposal theatrical scene, in the search for understanding how this viewer perceives and interprets the dramatic action. The empirical part of the research selected qualitative approach as methodology searching contributions of various pathways for field investigation and the interpretation of drawings, consistent with the dialogic, dynamic and interdisciplinary Art function. The theme of the research is a look on the look of the viewer. In the exercise of drawing a theatrical scene i discovered in the viewer, a designer. The viewer is a co-creator, a producer of meanings, not a mere discoverer. There is no passivity at reception. Perception-representation, reception-creation are integrated actions. Through the interpretation of the drawings was possible to see the viewer on her sensitive, symbolic dimension, far from merely explaining and rationalizing discourses of the verbal language. Theatre and design do not end in themselves, are ways to interpret, explore and experience the world. Mobilize the subjects to awaken its ability to designate, draw and design yourself, ordering, viewing and reviewing themselves, to explore, alone or in groups, their designs and drawings of the world and of themselves. Awareness of the importance and power of these knowledge can consolidate educational processes, investigations, actions and activities that add significant knowledge and can bring great leaps in human development in all its dimensions. The alliance between the theoretical framework and the interpretation of the material collected some significant conclusions about the interpretation of the viewer-designer were obtained, comprising a multiplicity of meanings expressed, the emphasis on specific aspects, the more distanced stance or identified with theatrical scenes, symbolic links with the elements and images present in the context of the scene and how the drawings reveal their creators and their sociocultural context.